Current Status and Future Perspectives of Axillary Management in the Neoadjuvant Setting - Kühn, Thorsten (Breast Care (Basel), 2018)
Axillary surgery has undergone considerable changes in recent years, especially in relation to patients who undergo neoadjuvant chemotherapy (NACT). Due to constantly decreasing rates of recurrence and death from breast cancer, modern surgical strategies aim at de-escalating the extent of local treatment and avoiding unnecessary procedures. This relates especially to lymph node surgery which is associated with considerable morbidity. In patients who initially present with clinically node-negative disease, sentinel lymph node biopsy (SLNB) is increasingly performed after NACT. The determination of the post-NACT nodal status does not only spare patients from additional surgery but also allows the assessment of pathologic complete response which is increasingly becoming an important tool for treatment planning. Since more than 70% of these patients have a ypN0 status after NACT, future trials will aim to identify patients who might be spared any axillary surgery after NACT. In patients who initially present with positive lymph nodes, the success rates of SLNB in terms of detection and accuracy are less favorable compared to those in patients who undergo primary surgery. The clinical significance of this is unclear. To reduce unnecessary axillary dissection in patients with cN1ycN0 status, prospective outcome data after SLNB without further lymph node removal are urgently needed. Improvements in surgical technique by localizing positive nodes at the time of diagnosis and removing them in a targeted surgical procedure (targeted axillary dissection) are under evaluation. Risk assessment and patient selection (including gene expression profiles) might be other ways of safely omitting axillary dissection.